Enhancing Sustainable Fintech Education: Investigating the Role of Smartphones in Empowering Economic Development in Jordan - Raed Alqirem; Raed Walid Al-Smadi (Discover Sustainability)
Abstract This study investigates the transformative role of smartphones in the financial technology (Fintech) industry in Jordan, focusing on how mobile technology enhances financial education and promotes broader adoption of Fintech services. This adoption plays a vital role in advancing specific United Nations Sustainable Development Goals (SDGs), notably SDG 1 (No Poverty), SDG 4 (Quality Education), and SDG 8 (Decent Work and Economic Growth), by fostering financial inclusion, enhancing digital financial literacy, and enabling equitable access to Fintech education through smartphones. Qualitative data was collected via an online survey distributed through social media platforms and emails, allowing for a broad and inclusive reach. The questionnaire targeted the overall public, or mobile phone users in Jordan, with no age restriction, to achieve diverse opinions regarding mobile-based financial literacy and Fintech adoption. One hundred eighty-nine valid responses were obtained, forming the basis for statistical analysis. The study explores the direct correlations between educational initiatives facilitated by smartphones and the subsequent adoption of Fintech services, considering the moderating effects of digital literacy and the regulatory environment. The results show that increased digital literacy enhances the effectiveness of Fintech applications, thus promoting financial inclusivity and literacy. The structural model explains 75.4% of the variance in smartphone usage for financial education (R2 = 0.754). Hypothesis testing confirms significant positive effects, with Fintech adoption (β = 0.033, p < 0.001), educational outreach (β = 0.040, p < 0.001), and innovation in educational Fintech products (β = 0.043, p < 0.001) associated with increased smartphone usage in education. The study highlights the need for advancements in user-friendly and accessible financial services, underlining the critical role of regulatory frameworks and digital literacy in fostering a secure and inclusive financial ecosystem. These findings are consistent with and support the SDGs, providing individuals with information and tools to maintain long-term financial stability.